?MEASUREMENT OF THERMAL CONDUCTIVITY OF MARBLE POWDER BY SPHERICAL SHELL METHOD (Biological Sciences - PJSIR, 1998)
Anapparatus,designed anddevelopedforthemeasurementofthermalconductivity 'K' ofpowdered materialbyspherical shellmethod,hasbeendescribed.ExtrapolationofstraightlinegraphofK-valueeagainstvaryingdensitiesofdifferentmesh sized powder materialgives K-valueoflumps of marble. Itdocs notgive K-valueof solid material because thedensity of compressed powdercannotbeequivalenttothedensityofnaturalmarble.K-valuesofdifferentmeshsizesmarblepowder have been determined and resultsarediscussed with referenceto thedata already availablein literature.